Axisymmetric temperature- and stress-dependent creep response of 'new' and 'old' HDPE geomembranes. Issue 3 (May 2005) - Merry, S. M.; Bray, J. D.; Yoshitomi, S.
Abstract : In this study, an axisymmetric tension test apparatus that is capable of performing constant-stress creep tests was used to compare the creep response of new and old HDPE geomembranes. Thirty-six-hour constant-stress creep tests were performed on new (about one year old) HDPE using a temperature range of 2–53°C and stresses ranging from 2 to 15 MPa. Excess material was then stored in a laboratory for an additional 7 years, after which time tests on 'old' geomembranes were performed. Because the experimental results could not be compared directly, an adaptation of the Singh–Mitchell creep model for soil, which is a rate process equation, was used to characterize the observed stress–strain–time–temperature response from the constant-stress creep tests over four logarithms of time. The model, which was calibrated using results on 'new' geomembranes, was used to predict the response of the 'old' geomembranes. It is shown that there was essentially no difference in the creep response of the old geomembranes.